PELAKSANAAN PIDANA MINIMUM KHUSUS DALAM PERKARA ANAK DI WILAYAH HUKUM PENGADILAN NEGERI PEKANBARU - Fauzi Rizky; Mukhlis R; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Setting a minimum penalty of this particular provide restrictions on freedom did the judge in the verdict , the District Court judge's ruling presence Pekanbaru containing about criminal punishment under the age of criminal defendants specifically towards children who are threatened specifically in violation of minimum criminal provisions of Article 81 paragraph ( 2 ) of Law Act No. 23 of 2002 on Child Protection. Then there are three formulation of the problem in writing this essay: How specialized in the implementation of minimum criminal case law child region of the District Court of Pekanbaru?, How considerations judges in criminal punishment under special minimum punishment in the case of children in the jurisdiction of the Court Pekanbaru country?, What barriers and efforts to overcome obstacles in the imposition of criminal punishment under special minimum in the case of children in the region of the Law Court of Pekanbaru?The research method in this study. Sociological type and legal research is descriptive. The location research of the District Court of Pekanbaru , sources supported by primary and secondary. The data collection techniques used were interviews and review of literature . After collected was then analyzed qualitatively , and draw conclusions with deductive thinking method is to analyze the problems of the general form to a specific shape.From the results of research and discussion, it can be concluded that , first , implementation of minimum criminal jurisdiction in the District Court of Pekanbaru there are 4 ( four ) children who are threatened criminal case specific minimum , one of which impose criminal punishment under special minimum . The second consideration is divided into 2 ( two ) , the consideration of judicial and non- judicial considerations . Third Barriers include : obstacles in terms of evidence and the scope of a certain age , mental limitations in the soul of the child testified in court , it is difficult to achieve peace , and effort to overcome barriers: law enforcement can corroborate the testimony of victims by using clues , while the child's limited mental ability in providing information , can be accompanied by an expert witness who is a psychologist, in terms of insiders, the judge approached the family of the victim so that the presence of peace .Keywords : Implementation of Special Minimum - Criminal – Child Case